2017
DOI: 10.1007/s00392-017-1185-z
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial injury after endovascular revascularization in critical limb ischemia predicts 1-year mortality: a prospective observational cohort study

Abstract: BackgroundPatients with critical limb ischemia (CLI) are at increased risk of cardiovascular complications and mortality. To determine (1) incidence of myocardial injury following endovascular revascularization, and (2) relationship between myocardial injury with 1-year mortality and major adverse cardiovascular events (MACE; i.e., composite of myocardial infarction, stroke, and death).Methods and resultsSingle-center, prospective cohort study of CLI patients ≥ 45 years of age, who underwent endovascular revas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 43 publications
0
37
0
Order By: Relevance
“…16,31 Also, in contrast to the findings reported by Saratzis et al, we found that both decreased preoperative eGFR level and length of surgery were independent predictors of AKI. 14 We hypothesize that the lower prevalence of perioperative AKI observed in our study group is likely explained by a difference in baseline characteristics between study cohorts and a larger sample size in our study (i.e., 267 patients in our cohort compared with 149 and 87 patients in cohorts by Saratzis et al and Pirgakis et al, respectively). It is also possible that patients whose postoperative creatinine level was not measured contributed to a lower incidence of AKI, although our sensitivity analyses did not suggest that these variables were missing not at random and that these patients would differ from the rest of the population.…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…16,31 Also, in contrast to the findings reported by Saratzis et al, we found that both decreased preoperative eGFR level and length of surgery were independent predictors of AKI. 14 We hypothesize that the lower prevalence of perioperative AKI observed in our study group is likely explained by a difference in baseline characteristics between study cohorts and a larger sample size in our study (i.e., 267 patients in our cohort compared with 149 and 87 patients in cohorts by Saratzis et al and Pirgakis et al, respectively). It is also possible that patients whose postoperative creatinine level was not measured contributed to a lower incidence of AKI, although our sensitivity analyses did not suggest that these variables were missing not at random and that these patients would differ from the rest of the population.…”
Section: Discussionmentioning
confidence: 66%
“…Szczeklik et al also described that myocardial injury is frequent in patients undergoing endovascular revascularization for critical limb ischemia, with a 25.5% incidence of myocardial injury after surgery. 14 Until now, little was known about the prevalence of myocardial injury in patients undergoing EVAR. In a small cohort study of 30 patients who underwent EVAR and had routine troponin T (TnT) measured 24 hr after their procedure, Davies et al showed that five patients (16%) experienced myocardial injury defined as a significant elevation of TnT levels and only one had chest pain with ischemic ECG changes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations